Perceptual constancy of pareidolias across paper and digital testing formats in neurodegenerative diseases - Gajanan S. Revankar; Tatsuhiko Ozono; Maki Suzuki; Hideki Kanemoto; Kota Furuya; Kazue Shigenobu; Kenji Yoshiyama; Yuki Yamamoto; Issei Ogasawara; Natsuki Yoshida; Susumu Iwasaki; Chizu Saeki; et al. (Heliyon)
Pareidolias refer to visual perceptual deficits where ambiguous shapes take on meaningful appearances. In neurodegenerative diseases, pareidolias are examined via a paper-based neuropsychological tool called the noise pareidolia test. In this study, we present initial findings regarding the utilization of pareidolia test on a digital format to analyze variations between paper-based and digital testing approaches. We performed our experiments on healthy controls, patients diagnosed with Alzheimer's disease (AD), Dementia with Lewy body disease (DLB) and Parkinson's disease (PD). Baseline MMSE assessments were conducted, followed by pareidolia testing using both paper-based tools and smartphones. Bland-Altman analysis was performed to evaluate the agreement between the two methods. We found that the illusionary phenomenon of pareidolia is consistent across paper and digital modalities of testing; that perceptual constancy is maintained across patient groups despite variations in image sizes; and pareidolic misperceptions, to some extent, are stabilized on a digital format. Our findings demonstrate a practical way of testing pareidolias on smartphones without compromising on the functionality of the test.